Following the ball: The migration of African soccer players across the Portuguese colonial empire, 1949-1975: By Todd Cleveland. Athens, OH: Ohio University Press, 2017 - Darby, Paul (Acta Academica: Critical views on society, culture and politics, 2018)
In Following the Ball, Todd Cleveland meticulously unpacks the history of African soccer players’ migratory journeys across the Portuguese colonial empire. While this book makes an invaluable contribution to what is a nascent body of literature on the migration of African football players, it also represents a telling addition to our understanding of the encounters between coloniser and colonised and how these played out specifically within the Portuguese colonial project.